Distinctive Categories of Evidentiality in certain English and Uzbek contexts (Eurasian Scientific Herald, 2022)
There are some verbal groups in the Uzbek language of which contextual meaning becomes clearer while analysing them in the aspect of evidentiality. Perceptual verbs emerge as a basic source in evidential analysis. The main reason of this might result in sharing the information by human perceptual senses such as see, hear or feel which are actively involved in the research paper. Therefore, perceptual verbs play a vital role in analysing evidential occurrence. Furthermore, we decided to discover the term evidentiality in the Uzbek language and to expose the category of evidentiality in the sample of Uzbek belles-lettres as it is initially being investigated in the Uzbek language. Evidential description plays essential role in sharing the information in both direct or indirect way. For instance, direct evidentiality is identified when the subject informs the others what he or she has observed whether was a direct witness of some action or event and shares the information which are accepted by senses. Whereas indirect evidentiality is considered as the basis of information which belongs to a totally another person, and is emerged from the talk with the secondhand or thirdhand